Rethinking cardiac surgical care in South Africa: A call for a dialogue - Meel, Ruchika (SA Heart Journal, 2026)
The editorial titled “Cardiac surgery in South Africa: Have we failed our legacy?” By Reddy et al. discusses the temporal transition of cardiothoracic surgery in South Africa.(1) Cardiothoracic surgery in South Africa has a strong international legacy, highlighted by the world’s first heart transplant in 1967. However, at present services are unevenly distributed, with most specialists and resources concentrated in urban private hospitals, while the public sector faces long waiting lists and limited capacity. Chris Hani Baragwanath Academic Hospital (CHBAH), the third largest hospital in the world, currently lacks onsite cardiothoracic surgical services and has not performed cardiac surgery for nearly 30 years.(2) All surgical cases are referred to the overburdened and under-resourced Charlotte Maxeke Johannesburg Academic Hospital.(2)